2019
DOI: 10.7202/1055565ar
|View full text |Cite
|
Sign up to set email alerts
|

Gestionnaires et diversité ethnoculturelle en milieu scolaire : une recherche-action/formation en contexte montréalais

Abstract: Les enjeux découlant de l'intensification de la mobilité internationale sont observables à l'échelle de plusieurs écoles et génèrent des défis au quotidien. Toutefois, de nombreux écrits soulignent le manque de formation des gestionnaires au regard des réalités rencontrées dans des milieux où les populations scolaires sont diversifiées. Dans la foulée de ces constats, nous avons mené une recherche-action/formation sur le leadership transformatif en milieu pluriethnique montréalais auprès de six gestionnaires e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This model of "differentiated" management is in line with Potvin's (2014) model for inclusiveness. Indeed, in the context of our participating principals, an inclusive systemic approach enabled them to adapt to their specific reality: the basic right to education, the existing religious, ethnocultural, and linguistic diversity, and the differentiated needs of their students, with fairness for all (Magnan et al, 2018). Ngwokabuenui (2013) arrived at similar conclusions in their study of anglophone-sector school leaders in Northwest Cameroon, as the principals in this region were also shown to develop school management practices that favored inclusion, which made it possible for them to take stock of their students with difficulties and special needs in their decision-making processes.…”
Section: The Context Of Diversitymentioning
confidence: 99%
“…This model of "differentiated" management is in line with Potvin's (2014) model for inclusiveness. Indeed, in the context of our participating principals, an inclusive systemic approach enabled them to adapt to their specific reality: the basic right to education, the existing religious, ethnocultural, and linguistic diversity, and the differentiated needs of their students, with fairness for all (Magnan et al, 2018). Ngwokabuenui (2013) arrived at similar conclusions in their study of anglophone-sector school leaders in Northwest Cameroon, as the principals in this region were also shown to develop school management practices that favored inclusion, which made it possible for them to take stock of their students with difficulties and special needs in their decision-making processes.…”
Section: The Context Of Diversitymentioning
confidence: 99%
“…However, despite the identification of possible room for maneuver within the school culture, in their respective articles, Borri-Anadon, Audet, and Lemaire, as well as Bauer, Aebischer, and Ribet showed that many systemic mechanisms of school culture contribute strongly to reproducing and reifying hierarchical school experiences, and to exacerbating processes of institutional discrimination to the disadvantage of immigrant and/ or racialized students-mechanisms tinged with an ethnocentric, even colorblind approach, masking unequal social relations between majority and minority groups. The challenge of rethinking the organization of selective streams to ensure equal access for allophone and/or immigrant students, and to avoid the segregation of school populations, as well as the challenge of reviewing assessment, grading, and guidance practices in order to deconstruct the mechanisms that produce inequalities and processes of exclusion, would, all in all, be colossal and require a certain managerial courage on the part of educational authorities [61,62] .…”
Section: Schools' Awareness Of Exclusion Processesmentioning
confidence: 99%
“…However, despite the identification of possible avenues for maneuver within school culture, in their respective articles, Borri-Anadon, Audet, and Lemaire, as well as Bauer, Aebischer, and Ribet, highlight that numerous systemic mechanisms of school culture strongly contribute to reproducing and reifying hierarchical school experiences and exacerbating institutional discrimination processes against students from immigrant backgrounds and/or racialized students -mechanisms tinged with an ethnocentric, or even colorblind, approach, masking unequal social relations between majority and minority groups. The challenge of rethinking the organization of selective pathways for equal access of allophone students and/or students from immigrant backgrounds, and to avoid the segregation of school populations, as well as the challenge of reviewing evaluation, classification, and orientation practices to deconstruct mechanisms of inequality production and exclusion processes, would, all in all, be colossal and would require a certain managerial courage from educational authorities [61,62] .…”
Section: School Actors Aware Of Exclusionary Processesmentioning
confidence: 99%